Menapaki Demokrasi dalam Sistem Protestan di Amerika Serikat - Lusi Handayani (Jurnal Iman dan Spiritualitas, 2022)
This study describes the dynamics of the development of the democratic system in Protestants. This study takes the writings of Paul Freston in a book entitled Religion and Politics. The method used in this research is qualitative, with library research involving books and other references related to the research topic. Data analysis was done by the comparative method. In this study, it is found that the development of Western democracy is indebted to the Protestant system in the past. This study also explains that America is one of the countries that is still developing the principles of democracy liberally. Still, the role of Protestants is getting less and less visible due to competition between churches and differences in interests in society. The political system that teaches interests above all else has changed the order of Protestant democracy taught in the Bible system as discussed in this study. Pure democratic values are no longer implemented. This is in line with the writings of Paul Freston and the discovery of information in reference sources.